Preparation of a Pectinase-Enriched Multienzyme under Solid State Fermentation of Sugarcane Bagasse - Othman M. Alzahrani; Muhammad Sohail; Samy F. Mahmoud; Amal S. Alswat; Yasser El-Halmouch (Fermentation, 2023)
Enzyme mediated degradation of lignocellulosic biomass is an important step in waste-biorefineries. Multienzyme preparations can effectively degrade complex materials and, hence, can be applied in biorefineries. Here, an agro-industrial waste, sugarcane bagasse, was used to produce a bacterial multienzyme. The bacterial strains including B. thuringiensis B45, B. velezensis BF3 and B. amyloliquefaciens B987 exhibited their growth at temperatures from 30–50 °C in the presence of 2% salt. The isolates B45, BF3 and B987 were able to produce endoglucanase, xylanase and pectinase, respectively. Therefore, it was aimed to obtain a multienzyme preparation by cultivating the bacterial consortium under a solid-state fermentation of untreated and chemically treated sugarcane bagasse. The results showed that the titres of cellulase and xylanase were generally higher when the strain B45 cultivated at the start of the fermentation. Interestingly, the degradation of cellulose and hemicellulose present in sugarcane bagasse by the strains B45 and BF3 rendered the mere pectin component available to the pectinolytic strain B987. The degradation of SB by the consortium was confirmed by gravimetric analysis and scanning electron microscopy. The study showed that the bacterial strains can be cultivated under solid-state fermentation to obtain industrially important enzymes.